Cre-activation in ErbB4-positive neurons of floxed Grin1/NMDA receptor mice is not associated with major behavioral impairment - Mallien, Anne Stephanie; Pfeiffer, Natascha; Vogt, Miriam A.; Chourbaji, Sabine; Sprengel, Rolf; Gass, Peter; Inta, Dragos (Frontiers in psychiatry, 2021)
Extensive evidence suggests a dysfunction of the glutamate NMDA receptor (NMDAR) in schizophrenia, a severe psychiatric disorder with putative early neurodevelopmental origins, but clinical onset mainly during late adolescence. On the other hand, pharmacological models using NMDAR antagonists and the clinical manifestation of anti-NMDAR encephalitis indicate that NMDAR blockade/hypofunction can trigger psychosis also at adult stages, without any early developmental dysfunction. Previous genetic models of NMDAR hypofunction restricted to parvalbumin-positive interneurons indicate the necessity of an early postnatal impairment to trigger schizophrenia-like abnormalities, whereas the cellular substrates of NMDAR-mediated psychosis at adolescent/adult stages are unknown. Neuregulin 1 (NRG1) and its receptor ErbB4 represent schizophrenia-associated susceptibility factors that closely interact with NMDAR. To determine the neuronal populations implicated in “late” NMDAR-driven psychosis, we analyzed the effect of the inducible ablation of NMDARs in ErbB4-expressing cells in mice during late adolescence using a pharmacogenetic approach. Interestingly, the tamoxifen-inducible NMDAR deletion during this late developmental stage did not induce behavioral alterations resembling depression, schizophrenia or anxiety. Our data indicate that post-adolescent NMDAR deletion, even in a wider cell population than parvalbumin-positive interneurons, is also not sufficient to generate behavioral abnormalities resembling psychiatric disorders. Other neuronal substrates that have to be revealed by future studies, may underlie post-adolescent NMDAR-driven psychosis.
Gesehen am 16.12.2021